The influence of the use of regulatory codes on the diagnosis of pathologies of reinforced concrete frame bridges - Lakhal Sebahi; Mohamed Bensoula; Mohamed Zaoui; Tahar Kadri (The Journal of Engineering and Exact Sciences)
The duration of utilization of bridges leads to its aging and therefore to the loss of some of their characteristics. Hence, the importance of specialized auscultation so that they can perform their function during the lifetime assigned to them. The safety of these bridges must also be ensured in view of the increase in the load of the heavy goods vehicles actually travelling and passing through them. The aim of this research is to study the influence of the utilization of the Algerian and the European regulatory codes on the diagnosis of the pathologies of reinforced concrete frame bridges. To achieve this goal, a frame bridge of total length of 37.2 m, located in the wilaya of Tiaret in Algeria, is expertized. It consists of two parts, one cast on site and the other prefabricated in reinforced concrete; it is classified of low seismicity and as an important bridge according to the Algerian seismic regulation. A diagnosis of the condition of the bridge was carried out on the basis of a preliminary visual inspection by making a schematic and photographic finding of the main issues and another inspection based on experimentation by carrying out several tests in situ and in the laboratory, which led to its classification in 2E according to the manual image of the quality of works of art (IQOA). Two types of regulatory loads are applied in this article; the Algerian regulation in force and the European regulation Eurocode 1 in order to carry out a comparative numerical simulation using the lowest compression constraint found during the experiment on the cores taken from the expert bridge. The results of this work confirmed the safety side of the European regulation because it responds correctly to the evolution of loads, hence any future verification of the pathological state of existing frame bridges must refer to the Eurocode as the loading code.